Monitoring or payroll maximization? What happens when workers enter the boardroom? - Cristi A. Gleason; Sascha Kieback; Martin Thomsen; Christoph Watrin (Review of Accounting Studies, 2021)
We examine whether worker representation on corporate boards results in improved monitoring or payroll maximization. Several economic theories predict that worker representatives would use control and voting rights in the boardroom to transform firm assets into private benefits and increased wages, but labor contract models suggest that workers' inside information should permit improved monitoring. To investigate this conflict, we use mandatory worker representation on corporate boards in Germany. Using hand-collected data, our results suggest that the worker representatives' payroll maximization incentives dominate their monitoring duties. Specifically, worker representatives reduce real earnings management when it results in wage cuts or job losses but not when it increases payroll or job security. Similarly, worker representatives are generally associated with improved monitoring of tax planning activities. However, when the risk of offshoring jobs is high, worker representatives do not promote tax planning for low-aggression firms and instead block aggressive tax planning for high-aggression firms. This evidence helps policymakers and researchers better understand the role of workers in corporate governance systems and contributes to the ongoing public debate about introducing worker representation in the United States and the United Kingdom.
Keywords: G34; H25; K34; M41; M43; 650; Worker representation; Monitoring; Payroll maximization; Agency conflict; Corporate governance; Earnings management; Tax avoidance